Epidemiologie des Diabetes - Jacobs, Esther; Rathmann, Wolfgang (Diabetologie und Stoffwechsel, 2017)
For Germany, estimates for diabetes prevalence, incidence, morbidity and mortality are based on different study types, e. g. regional population-based studies, surveys or health claims data, and various methods are used for the calculations. Thus, there are a number of different epidemiological estimates published. This is also true for the prevalence of people with undiagnosed diabetes and prediabetes. In addition, evidence exists that the prevalence of diabetes varies between regions in Germany. In this context, new risk factors, such as regional deprivation and air pollution, are currently in the focus. This article gives a short overview on the current research status in diabetes epidemiology with regard to the situation in Germany. Trends in the development of diabetes, its complications and mortality are also discussed. Based on the current refugee situation, the article contains a short insight of available studies on this topic. The overview on the current evidence is supplemented by methodological aspects that should be taken into account when interpreting studies.
Keywords: Epidemiologie; Diabetes; Typ-2-Diabetes; Risikofaktoren; Mortalität